Effect of small-sided games and repeated shuffle sprint training on physical performance in elite handball players - Dello Lacono, A.; Ardigò, L. P.; Meckel, Y.; Padulo, J. (The Journal of Strength and Conditioning Research, 2016)
This study was designed to compare the effects of small-sided games (SSGs) and repeated shuffle sprint (RSS) training on repeated sprint ability (RSA) and countermovement jump (CMJ) tests performances of elite handball players. Eighteen highly trained players (24.8 ± 4.4 years) were assigned to either SSG or RSS group training protocols twice a week for 8 weeks. The SSG training consisted of 5 small-sided handball games with 3-a-side teams excluding goalkeepers. The RSS consisted of 2 sets of 14-17 of 20-m shuttle sprints and 9-m jump shots interspersed by 20-second recoveries. Before and after training, the following performance variables were assessed: speed on 10-m and 20-m sprint time, agility and RSA time, CMJ height, standing throw, and jump shot speed. Significant pre-to-post treatment improvements were found in all the assessed variables following both training protocols (multivariate analysis of variance, p = 0.05). There was a significantly greater improvement on 10-m sprint, CMJ, and jump shooting, after the RSS in comparison with SSG training (+4.4% vs. +2.4%, +8.6% vs. +5.6%, and +5.5% vs. +2.7%, respectively). Conversely, agility and standing throwing showed lower improvements after RSS in comparison with SSG (+1.0% vs. +7.8% and +1.6% vs. +9.0%, respectively). These results indicate that these training methods are effective for fitness development among elite adult handball players during the last period of the competitive season. Specifically, SSG seems to be more effective in improving agility and standing throw, whereas RSS seems preferable in improving 10-m sprint, CMJ, and jump shot.